Safety Analysis against Tsunami Attacks at a Nuclear Power Plant Site - Jeong-Wook Seo; Jin Woo Lee; Yong-Sik Cho (Journal of Applied Mathematics)
Several nuclear power plants are now under operation, and more plants will be built along the eastern coast of the Korean Peninsula. These nuclear power plant sites may be vulnerable to unexpected tsunami attacks. In this study, a coupled numerical model based on the shallow-water theory was employed to analyze the safety of the Uljin Nuclear Power Plant site against three historical and eleven virtual tsunami attacks. The numerical model consisted of a transoceanic propagation and an inundation model. Both models were discretized by the finite difference method. Maximum and minimum tsunami heights were estimated for the three historical and eleven virtual tsunamis. The obtained results showed that the Uljin Nuclear Power Plant site would be safe against the tsunami attacks included in this study.